2016
DOI: 10.1002/2015rs005814
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of ducts observed over a tropical station, Gadanki, using high‐resolution GPS radiosonde observations

Abstract: A comprehensive study on diurnal variation of ducting using high vertical and temporal resolution radiosonde measurements over the Indian tropical region, Gadanki (13.5°N, 79.2°E), was presented. The diurnal variation of ducts was examined statistically based on both the refractivity and modified refractivity using 3-hourly radiosonde soundings obtained during October 2010 to March 2014 as a part of tropical tropopause dynamics (TTD) campaigns conducted under Climate and Weather of Sun Earth System (CAWSES) In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Due to the complex terrain surrounding the radar site, the LLJs are strong during night hours generating strong wind shears and associated strong turbulence. This type of deep nocturnal boundary layer (boundary layer from sunset to sunrise referred to as NBL) has also been observed by Basha and Venkat Ratnam [2009] and Manjula et al [2016] over this region . Stull [1988] also reported that the NBL height is mostly dictated by the radiative cooling at the surface, by the strength of eventually present LLJs and associated turbulence, and residual layer.…”
Section: Efficacy Of the Tfl Methodsmentioning
confidence: 99%
“…Due to the complex terrain surrounding the radar site, the LLJs are strong during night hours generating strong wind shears and associated strong turbulence. This type of deep nocturnal boundary layer (boundary layer from sunset to sunrise referred to as NBL) has also been observed by Basha and Venkat Ratnam [2009] and Manjula et al [2016] over this region . Stull [1988] also reported that the NBL height is mostly dictated by the radiative cooling at the surface, by the strength of eventually present LLJs and associated turbulence, and residual layer.…”
Section: Efficacy Of the Tfl Methodsmentioning
confidence: 99%
“…The phenomenon is caused by the gradient in refractivity with regard to altitude. Many meteorological processes are associated with it, like temperature inversion, moisture inversion, the subsidence of air masses, and the passing of cold air over warm land (Manjula et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the data from GPS dropsondes, aircraft and radiosondes were used in the literature. Manjula et al analyzed the diurnal variation of atmospheric ducts in different seasons and the ducts characteristics contrast between different seasons in Gadanki [10]. Zhao et al [11] used radiosonde data on the balloons by ship to detect the ducts occurrence in 2013, and they concluded that the probability of ducts in the South China Sea is about 75% during 2010-2012.…”
Section: Introductionmentioning
confidence: 99%